Disruption in financial reporting : a post-pandemic view of the future of corporate reporting - Bhaskar, Krish N., 1945-; Flower, John, 1934- (London : Routledge, 2021)
"Since the global financial crisis of 2007-8, new laws and regulations have been introduced with the aim of improving the transparency in financial reporting. Yet the flow of meaningful information to shareholders and the public has deteriorated. This concise book argues that the changes have simply masked an increase in the use of corporate PR and impression management simulacra which allow poor performance to be masked by misleading information presented in glib boilerplate texts and tables. Drawing on extensive research and interviews with insiders and experts, this book charts what has gone wrong with financial reporting and offers a range of solutions to improve information to both investors and the public. Providing a compelling exploration of the industry's failings and present difficulties, and the impact of future disruption this timely thought provoking book will be of great interest to students, researchers, professionals and policy makers in accounting, financial reporting, financial statement analysis and governance"--
Includes bibliographical references.
Keywords: Financial statements; Corporations -- Finance; Auditing